2020
DOI: 10.1177/0954406220978250
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of temperature compensation for piezoelectric sensor bonded to AISI-1080 material

Abstract: Electromechanical impedance (EMI) method has been widely used to evaluate structural health in recent years. In this method inexpensive, small, easy to apply, lightweight piezoelectric sensors are used to observe the changes in the structures. Different environmental conditions affect the piezoelectric sensor and the structure significantly. If the environmental impact is neglected, it causes misinterpretations as if it were present, although there is no construction defect. Therefore, it is necessary to compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous studies stated that the measurement temperature has a significant effect on adhesive layer rigidity for especially thick adhesive layers; the adhesive could suppress the vibrations and affect admittance signals. The researchers reported that the temperature effect could be compensated by conducting controlled experiments (Tekkalmaz et al, 2021b). In the current study, in order to eliminate the effects of ambient conditions, all the samples from the same group were repeatedly tested on the same day at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies stated that the measurement temperature has a significant effect on adhesive layer rigidity for especially thick adhesive layers; the adhesive could suppress the vibrations and affect admittance signals. The researchers reported that the temperature effect could be compensated by conducting controlled experiments (Tekkalmaz et al, 2021b). In the current study, in order to eliminate the effects of ambient conditions, all the samples from the same group were repeatedly tested on the same day at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…One of the external noises is the temperature sensitivity of the method. The previous study on the topic shows that different temperatures can affect the EMI measurements, but this effect can be compensated (Tekkalmaz et al, 2021b; Zhang et al, 2019), but it requires many controlled measurements. Another external noise source is vibrations that may arise during usage.…”
Section: Introductionmentioning
confidence: 99%
“…The EMI technique is also being used in other fields such as shear thickening fluids (Haydarlar et al, 2021a), composite structures (Gu¨emes et al, 2020) and turning process of materials (Sofuog˘lu et al, 2022). There are various damage detection algorithms have been developed based on frequency-warping (Kexel and Moll, 2022), curve fitting (Haydarlar et al, 2021b), cumulative electric power (Soman et al, 2020) and others methods (Tekkalmaz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In order to alleviate the influence of EOC in SHM applications, a couple of compensation methods have been proposed (Croxford et al, 2010; Douglass and Harley, 2018; Tekkalmaz et al, 2020; Wandowski et al, 2017) which involve different types of searches for an optimal alignment. In contrast to static distances, such as root-mean-square deviation, mean absolute distance (MAD), correlation coefficient (Tekkalmaz et al, 2020) or cumulative power (Soman et al, 2020), here distances that originate from a dynamic process, like optimization and/or search, are referred to as a dynamic distance.…”
Section: Introductionmentioning
confidence: 99%